OPTIMAL CUT-OFF POINTS OF INSTANTANEOUS WAVE-FREE RATIO IN THE ASSESSMENT OF THE FUNCTIONAL SIGNIFICANCE OF CORONARY ARTERY STENOSES USING NONINVASIVE METHODS AS REFERENCE - D. I. Darenskiy; V. V. Gramovich; E. A. Zharova; M. G. Mitroshkin; R. V. Atanesyan; G. N. Bakashvili; Y. G. Matchin (Евразийский Кардиологический Журнал)
ABSTRACT Objective: the aim of our study was to determine the optimal instantaneous wave-free ratio (iFR) cut-off points in assessing the functional significance of intermediate coronary artery stenoses in patients with chronic coronary artery diseases (CAD) using non-invasive methods of myocardial ischemia verification as reference. Methods: 60 patients with chronic CAD or suspected CAD and intermediate coronary stenoses (50-70%) were included in the study. 92 borderline coronary stenoses were investigated. iFR measurement was carried out within 10 days after the non-invasive stress test (a combination of stress echocardiography and SPECT). Results: stress-induced myocardial ischemia was detected in 18 patients (30%). iFR values are in the range 0.68 to 1.0, median of iFR - 0.95 [0.9; 0.99]. Area under iFR ROC-curve - 0.95 ± 0.02 (95%CI: 0.885-0.985). The iFR cut-off point 0.92 is optimal and has a sensitivity of 100%, a specificity of 83% and a negative predictive value (NPV) of 100%. The iFR cut-off point 0.86 is associated with a specificity of 100%, a sensitivity of 33% and a positive predictive value of 100%. The values of iFR «grey» zone ranged from 0.87 to 0.92. Conclusion: using non-invasive methods of verification of myocardial ischemia as a reference, iFR cut-off point 0.92 excludes the functional significance of coronary artery stenosis with a NPV of 100%. iFR cut-off point 0.86 confirms the functional significance of the stenosis with a PPV of 100%. It is recommended to measure the fractional flow reserve in the case of obtaining the iFR values of «grey» zone (0,87-0,92). Key words: iFR, CAD, stress-echo, SPECT.